СИСТЕМА АВТОМАТИЗИРОВАННОГО КОНТРОЛЯ НЕФТЕПРОВОДА - Леготкина, Татьяна Сергеевна; Хижняков, Юрий Николаевич (Вестник ИжГТУ имени М.Т. Калашникова, 2014)
A system of automatic control of the oil pipeline based on OCR technology is proposed. The system can handle multiple oil pipelines, and has the ability to manipulate the data on the parameters of oil, to display in a convenient way the data on the oil pipeline profile and the pressure profile. On the basis of the data, the system checks for leaks and determine the leak.